GC analysis of organotin compounds using pulsed flame photometric detection and conventional flame photometric detection - Godoi, AFL; Favoreto, R.; Santiago-Silva, M. (Vieweg, 2003)
Organotin compounds, largely used as biocides in antifouling paints, are among the most toxic materials introduced into the aquatic environment. Sensitive analytical methods are thus required to characterize their occurrence in environmental and biological matrices. The comparison between two different photometric detectors in terms of analytical performance was carried out for the analysis of organotin compounds. A flame photometric detector (FPD) and a pulsed flame photometric detector (PFPD) were optimized. Their respective sensitivity, linearity range and selectivity were evaluated. Limits of detection obtained for a tributyltin compound (TBT) were 5.0 and 0.9 pg (as Sn) for the FPD and PFPD, respectively, using a 390 nm filter. The PFPD showed higher selectivity, besides reduced gas consumption in the flame, and is very attractive for organotin compound speciation in complex environmental matrices.
Keywords: gas chromatography; flame photometric detector; pulsed flame photometric detector; organotin compounds; antifouling paints